Oncolytic rodent protoparvoviruses evade a TLR- and RLR-independent antiviral response in transformed cells - Angelova, Assia L.; Pierrard, Kristina; Detje, Claudia N.; Santiago, Estelle; Grewenig, Annabel; Nüesch, Jürg P. F.; Kalinke, Ulrich; Ungerechts, Guy; Rommelaere, Jean; Daeffler, Laurent (Pathogens, 2023)
The oncolytic rodent protoparvoviruses (PVs) minute virus of mice (MVMp) and H-1 parvovirus (H-1PV) are promising cancer viro-immunotherapy candidates capable of both exhibiting direct oncolytic activities and inducing anticancer immune responses (AIRs). Type-I interferon (IFN) production is instrumental for the activation of an efficient AIR. The present study aims at characterizing the molecular mechanisms underlying PV modulation of IFN induction in host cells. MVMp and H-1PV triggered IFN production in semi-permissive normal mouse embryonic fibroblasts (MEFs) and human peripheral blood mononuclear cells (PBMCs), but not in permissive transformed/tumor cells. IFN production triggered by MVMp in primary MEFs required PV replication and was independent of the pattern recognition receptors (PRRs) Toll-like (TLR) and RIG-like (RLR) receptors. PV infection of (semi-)permissive cells, whether transformed or not, led to nuclear translocation of the transcription factors NFĸB and IRF3, hallmarks of PRR signaling activation. Further evidence showed that PV replication in (semi-)permissive cells resulted in nuclear accumulation of dsRNAs capable of activating mitochondrial antiviral signaling (MAVS)-dependent cytosolic RLR signaling upon transfection into naïve cells. This PRR signaling was aborted in PV-infected neoplastic cells, in which no IFN production was detected. Furthermore, MEF immortalization was sufficient to strongly reduce PV-induced IFN production. Pre-infection of transformed/tumor but not of normal cells with MVMp or H-1PV prevented IFN production by classical RLR ligands. Altogether, our data indicate that natural rodent PVs regulate the antiviral innate immune machinery in infected host cells through a complex mechanism. In particular, while rodent PV replication in (semi-)permissive cells engages a TLR-/RLR-independent PRR pathway, in transformed/tumor cells this process is arrested prior to IFN production. This virus-triggered evasion mechanism involves a viral factor(s), which exert(s) an inhibitory action on IFN production, particularly in transformed/tumor cells. These findings pave the way for the development of second-generation PVs that are defective in this evasion mechanism and therefore endowed with increased immunostimulatory potential through their ability to induce IFN production in infected tumor cells.
Gesehen am 14.06.2023